2023
DOI: 10.1039/d2nj04862k
|View full text |Cite
|
Sign up to set email alerts
|

Macroemulsion-mediated synthesis of fibrous ZnO microrods and their surface morphology contribution to the high photocatalytic degradation rate

Abstract: In this work, fibrous ZnO microrods were synthesized through a macroemulsion-mediated solvothermal method using two different precursors: zinc nitrate and zinc acetate. Initially, we optimized the urea concentration using the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…ZnO and its derivatives have emerged as a central research topic in scientific investigations in recent years, and these materials have been highlighted for their potential application in different fields such as medicine, cosmetics, textiles, food, electronics, materials sciences, optics, ceramics, and drug delivery. 1–5 The wide application of these materials could be realized through their unique properties, such as wideband gap, 6 oxygen-deficient nature, 7 splendid morphological availability, 8 large surface area, 9 strong adsorption ability, 10 less toxic nature, 11 good biocompatibility, 12,13 and high anti-microbial activity. 14 Among these, the photocatalytic property of ZnO has shown promising potential for many environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO and its derivatives have emerged as a central research topic in scientific investigations in recent years, and these materials have been highlighted for their potential application in different fields such as medicine, cosmetics, textiles, food, electronics, materials sciences, optics, ceramics, and drug delivery. 1–5 The wide application of these materials could be realized through their unique properties, such as wideband gap, 6 oxygen-deficient nature, 7 splendid morphological availability, 8 large surface area, 9 strong adsorption ability, 10 less toxic nature, 11 good biocompatibility, 12,13 and high anti-microbial activity. 14 Among these, the photocatalytic property of ZnO has shown promising potential for many environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in our previous work, a simple in situ photocatalytic degradation of rhodamine B using a photoluminescence spectroscopic technique under ultraviolet (UV) irradiation at 365 nm was performed. 38,39 The photocatalytic degradation kinetics was determined by measuring the decay of photoluminescence intensity with respect to the irradiation time. We found that the samples with a lamellar surface morphology provide better photocatalytic activity under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using a deep eutectic solvent as a template, Liu et al synthesized flower-like ZnO nanoparticles with higher photocatalytic performance for the degradation of methyl orange through a simple hydrothermal method [ 17 ]. Benu et al synthesized fibrous ZnO microrods with higher photocatalytic efficiency for the degradation of RhB through a macroemulsion-mediated solvothermal method using zinc nitrate and zinc acetate as precursors [ 18 ]. The detailed synthesis conditions, experimental variables, and morphologies of the various aforementioned strategies are presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%